Princess Princess ever after - O'Neill, Katie (Cartoonist); Yarwood, Ari (Oni Press, Inc., 2016)
When the heroic princess Amira rescues the kind-hearted princess Sadie from her tower prison, neither expects to find a true friend in the bargain. Yet as they adventure across the kingdom, they discover that they bring out the very best in the other person. They'll need to join forces and use all the know-how, kindness, and bravery they have in order to defeat their greatest foe yet: a jealous sorceress with a dire grudge against Sadie. Join Sadie and Amira, two very different princesses with very different strengths, on their journey to figure out what happily ever after really means and how they can find it with each other.